Peningkatan Hasil Belajar Biologi Siswa Madrasah Aliyah Menggunakan Model Pembelajaran Self Organized Learning Environments (SOLE) - Sahriah Sahriah; Novita Aulia Ramadani; Ahmad Yani (IAIN Ternate, 2022)
This research is motivated by teaching and learning activities which are mostly teacher-centered due to the selection of models and methods that are not appropriate with the material presented by the subject teacher, so that student learning outcomes are low, especially in biology subjects in class XI MIPA 2 Madrasah Aliyah Muhammadiyah Sengkang, Wajo Regency. This study aims to determine the improvement of biology learning outcomes through photographic media with a combination of the Sole learning model (Self Organized Learning Environments) for class XI MIPA 2 Madrasah Aliyah Muhammadiyah Sengkang. This type of research is classroom action research (Classroom Action Research) involving repeated self-reflection, namely planning, implementing actions, observing/observing, and reflecting. This research was carried out in two cycles, where between cycle I and cycle II were a series of interrelated activities. This research was conducted in the even semester of the 2020/2021 academic year in March for students of class XI MIPA 2 Madrasah Aliyah Muhammadiyah Sengkang with a total of 20 students. The data collected are quantitative and qualitative data. The instruments used in this study were student activity observation sheets and learning outcomes test questions in the form of essay questions. The results showed that the application of the Sole learning model (Self Organized Learning Environments) could improve student learning outcomes in biology class XI MIPA 2 Madrasah Aliyah Muhammadiyah Sengkang. This is evidenced by the average value of learning outcomes in the first cycle, which is 76.50%, increasing in the second cycle to 89.00%. While the number of students who reached the KKM in the first cycle was 8 people and increased in the second cycle to 20 people.Keywords: learning outcomes, SOLE learning model.